Topical Delivery of Ceramide by Oil-in-Water Nanoemulsion to Retain Epidermal Moisture Content in Dermatitis - Yu Zhou; Lichun Wu; Yi Zhang; Jia Hu; Jannatul Fardous; Yasuhiro Ikegami; Hiroyuki Ijima (Biomolecules)
External environmental stressors and internal physiological changes frequently compromise the skin barrier, resulting in conditions such as dermatitis and dehydration. A key underlying factor is the depletion of ceramides, essential lipids in the stratum corneum that maintain skin integrity. Although topical ceramide supplementation is effective for barrier repair, its clinical application is limited by poor solubility and low skin permeability. To overcome these challenges, this study developed an oil-in-water nanoemulsion (O/W-NE) using ultrasonic emulsification for the efficient transdermal delivery of ceramide C2. Octyldodecanol was selected as the oil phase to enhance ceramide solubility, while glycerin was incorporated to increase aqueous phase viscosity, reduce particle size, and function as a biocompatible penetration enhancer. The optimized nanoemulsion achieved a particle size of 112.5 nm and an encapsulation efficiency of 85%. Its performance was evaluated via in vitro release, ex vivo skin permeation, and in vivo biocompatibility studies. Mechanistic investigations revealed that both particle size and glycerin concentration significantly influenced ceramide penetration into the epidermis and dermis. Additionally, the nanoemulsion exhibited moisturizing and barrier-repair effects in a damaged skin model. Overall, this O/W-NE offers a stable, non-invasive strategy for enhancing ceramide delivery and restoring skin barrier function.